A biomass-derived N-doped porous carbon catalyst for the aerobic dehydrogenation of nitrogen heterocycles. (5th January 2022) - Liu, Jing-Jiang; Guo, Fu-Hu; Cui, Fu-Jun; Zhu, Ji-Hua; Liu, Xiao-Yu; Ullah, Arif; Wang, Xi-Cun; Quan, Zheng-Jun
Abstract : N-doped porous carbon (NC) was synthesized from sugar cane bagasse, which is a sustainable and widely available biomass waste. Abstract : N-doped porous carbon (NC) was synthesized from sugar cane bagasse, which is a sustainable and widely available biomass waste. The preferred NC sample had a well-developed porous structure, a graphene-like surface morphology and different N species. More importantly, the heterogeneous carbocatalyst exhibited superior catalytic performance in the aerobic dehydrogenation of various heterocyclic nitrogen compounds (49 examples, up to 96% yield), similar to that of C3 N4 and GO. Characterization by TEM, BET and XPS accompanied by the EPR analysis revealed that the enhanced catalytic properties of NC came from its high activation ability for both O2 and heterocyclic nitrogen, attributed to the porous structure and pyridinic N (N-6) species, respectively.